Analisis Literasi Kewirausahaan Mahasiswa Sekolah Tinggi Ilmu Ekonomi Jambi - Prayetno Agustinus Sitanggang; Henky Setiadi; Friska Artaria Sitanggang (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study aims to analyze literacy entrepreneurship of students college. The respondens in this research is Students of Sekolah Tinggi Ilmu Ekonomi Jambi (STIE Jambi), sample was taken by purposive sampling techniques with number of samples in this study amounted to 100 respondents. The research method used a survey method through questionnaires distributed to STIE Jambi students who became research respondents. The instrument used to measure the entrepreneurship literacy Student is a questionnaire with questions consisting of several indicators, namely: basic knowledge of entrepreneurship, knowledge of business ideas and opportunities, and knowledge of business aspects. This research uses quantitative methods with descriptive research types. The data used is primary data obtained through a questionnaire on a likert scale. The results indicated that entrepreneurship literacy students of STIE Jambi were all in the categories of excellent, namely with the value of the amount percentage 82% for indicators of basic entrepreneurship knowledge, 81% for indicators of knowledge of ideas and business opportunities, and 83% for average indicators of knowledge about business aspects.